Biomechanical Measurements in the Spinal Column - Quaresma, C. (2012)
In modern society, pain is a relevant problem of the population in general and of pregnant women in particular, being a common symptom and frequently referred to in pregnancies without any pathology associated. Studies indicate that from 35 to 76% of pregnant women experience pain during the gestational period. Most researchers attribute the etiology of the pain to biomechanical alterations of the spinal column throughout pregnancy, however an in-depth analysis has been delayed by the fact that the analytical processes involved are invasive and, as such, cannot be applied to pregnant women. On the other hand, non-invasive diagnostic methods only allow partial analyses of the spinal column, not offering a global vision. In face of the limitations mentioned we built Vertebral Metrics – an instrument that allows us to identify the x, y and z positions of each of the vertices of the spinal apophyses (vertebrae), giving us a global evaluation of the spinal column, in a standing position. The present work has the objective of presenting the first application of this equipment to 49 pregnant women at four different moments of pregnancy (12, 20, 32 e 37 weeks of gestation). Analyzing the results we can conclude that Vertebral Metrics – is an innovative instrument in the global evaluation of the spinal column in a standing position, allowing a quantitative analysis of its shape and temporal variations.